The hydrologic regime of Mackenzie River and connection of "no-closure" lakes to distributary channels in the Mackenzie Delta, Northwest Territories - Burn, C. R. (Canadian Journal of Earth Sciences, 1995)
Mackenzie Delta lakes have been classified by the seasonal duration of their connection to Mackenzie River. "No-closure" lakes are determined on the basis of minimum summer water level. Such lakes may become disconnected from the Mackenzie in autumn or winter, as water level falls or if the sills between lakes and distributary channels are frozen through and so sealed. Water level in the central delta rises continuously after late November–early December, at first because discharge into the delta increases once the Mackenzie drainage basin has frozen over, and then as sea and channel ice thickens in the outer delta, impounding discharge. Since 1973 this seasonal increase in stage from its minimum in early December to the level on 1 April has been between 29 and 95 cm. Between 1987 and 1994, the rise in stage near Inuvik has been slightly greater than increases in lake-ice thickness (30–68 cm). Channels and lakes that are connected to the Mackenzie discharge system in December may remain connected throughout winter. A critical sill elevation for connection of such lakes to the river system is the minimum stage minus mid-December ice thickness. Recently, these elevations have been from 1.0 to 1.6 m lower than late summer water levels. Lakes with sill elevations still lower may remain connected to the Mackenzie throughout the year. In 1993-1994, only 3 of 16 "no-closure" lakes surveyed near Inuvik remained open to the Mackenzie discharge throughout winter, representing 2% of the lakes in this portion of the delta.